Pendidikan Kesehatan melalui Animasi: Upaya Meningkatkan Keterampilan Cuci Tangan Cegah Diare pada Anak Sekolah Dasar - Rizky Amelia Astuti; Nina Mardiana; Bernadetha Bernadetha (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Diarrhea is an infectious disease and a health problem worldwide, including Indonesia. Handwashing with soap (HWWS) is an important step to prevent diseases such as diarrhea. Animated videos are an effective medium to deliver health education aimed at improving practical skills. This study evaluated the effect of health education through animated video intervention on HWWS skills in school-age children. This study used a quasi-experimental pre-posttest method with a control group design. Forty students were sampled using simple random sampling and divided into experimental and control groups. Animated videos were used as an intervention for the experimental group, while posters were used for the control group. HWWS skills were assessed using an observation checklist before and after the intervention. Data were analyzed by Wilcoxon signed-rank test and Mann-Whitney U test. The results of statistical analysis showed a significant effect (p-value = 0.000) of health education in the form of animated videos on students' HWWS skills, the results of statistical analysis also showed a statistically significant difference (p value = 0.000) in students' HWWS skills in the experimental group and control group after being given health education with different media. Schools are expected to develop animated videos as a medium to increase exposure and quality of health education.